INTENTION TO INVEST IN FINANCIAL PRODUCT OF OLDER PRERETIREES WITH FINANCIAL SELF EFFICACY AS AN INTERVENING VARIABLE - Liza Handoko; vina christina nugroho; Jacquelinda Sandra Sembel (Universitas Multimedia Nusantara, 2020)
Abstract- This research wants to investigate the effect of financial knowledge, basic individual traits and compound traits towards intention to invest of pre-retirees with the intervening variable of financial self-efficacy. Older pre-retirees have unique psychological and economic position, as they experience their highest level of lifetime earnings while nearing the end of their financial life cycle. Older pre-retirees must find ways to self-regulate their financial environment. One way to deal with this is through the investment scheme. We use modified model to know the factors that affect intention to invest based on their knowledge and personality, with financial self-efficacy as the intervening variable. We involved 160 respondents of 45 years old and older. The result showed that all the hypothesis is rejected except financial knowledge which is positively associated with intention to invest. This result presents that pre-retirees in Indonesia who have good financial knowledge will have intention to invest in financial products. Keywords: Pre-retirees, intention to invest, financial self-efficacy